Short communication: Leaf architecture of 35 species of Dipterocarpaceae cultivated in Forest Area with Special Purposes in Carita, Banten, Indonesia - ALNUS MEINATA; MOHAMMAD NA’IEM; DWI TYANINGSIH ADRIYANTI; ATUS SYAHBUDIN (Society for Indonesian Biodiversity, 2021)
Abstract. MeinataA, Na’iem M, Adriyanti DT, Syahbudin A. 2021. Short communication: Leaf architecture of 35 species of Dipterocarpaceae cultivated in Forest Area with Special Purposes in Carita, Banten, Indonesia. Biodiversitas 22: 2952-2960. Dipterocarpaceae is a major commercial timber characterized by high unbranched bole, paired stipules, and winged fruit. The identification process in the family becomes problematic, in cases where the generative organ is absent. Therefore, a new approach needs to be established to address any misidentification leading to improper utilization. This study aims to determine the leaf architecture in 35 species of Dipterocarpaceae cultivated in Forest Area with Special Purposes (KHDTK) Carita, Banten, Indonesia. The ten leaf samples collected were the third and fourth leaves from terminal shoots of a single tree of each species. Subsequently, the data were observed and measured based on the 17 morphological characters. Each character was then scored and analyzed using multivariate analyses cluster to determine the relationship between species. Dipterocarpaceae generally has pinnate leaf category, geniculate petiole, and entire margin. Furthermore, the phenon line in the dendrogram is cut at 0.695 similarity level to establish meaningful interpretation. The 35 species observed were grouped into 4 major clusters. Small leaf group, inconsistent tertiary vein pattern group, symmetrical leaves with cordate base leaf group, and other groups that do not resemble mentioned characters. The key determination comprised 34 couplets with three characters repeated due to limited descriptors.